Mikroobdelava silicija - Resnik, Drago (Vakuumist, 1998)
Within this paper, several principles, tools and technologies that are employed in microstructuring of 3-D silicon sensing and actuating devices are reviewed. Furthermore, mechanism of anisotropic wet etching of silicon in potassium hydroxide (KOH), wich is considered at the most frequently used etchant is summarised. Beside the electrochemical etch stop technique, also problems of convex corner compensation are considered and some of our related results are discussed and presented.
Keywords: silicij; mikroobdelava; jedkanje; bondiranje